A Citation-Based Analysis and Review of Significant Papers on Timing and Time Perception - Teki, Sundeep (Frontiers in Neuroscience, 2016)
Time is an important dimension of brain function, but little is yet known about the underlying cognitive principles and neurobiological mechanisms. The field of timing and time perception has witnessed tremendous growth and multidisciplinary interest in the recent years with the advent of modern neuroimaging and neurophysiological approaches. In this article, I used a data mining approach to analyze the timing literature published by a select group of researchers (n = 202) during the period 2000-2015 and highlight important reviews as well as empirical articles that meet the criterion of a minimum of 100 citations. The qualifying articles (n = 150) are listed in a table along with key details such as number of citations, names of authors, year and journal of publication as well as a short summary of the findings of each study. The results of such a data-driven approach to literature review not only serve as a useful resource to any researcher interested in timing, but also provides a means to evaluate key papers that have significantly influenced the field and summarize recent progress and popular research trends in the field. Additionally, such analyses provides food for thought about future scientific directions and raises important questions about improving organizational structures to boost open science and progress in the field. I discuss exciting avenues for future research that have the potential to significantly advance our understanding of the neurobiology of timing, and propose the establishment of a new society to promote open science and collaborative work within the highly diverse and multidisciplinary community of researchers in the field of timing and time perception.